1998
DOI: 10.1677/joe.0.1560307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal dexamethasone administration on thermoregulation in lambs delivered by caesarean section

Abstract: We have previously shown that lambs delivered by caesarean section 1 week prematurely become hypothermic due to reduced brown adipose tissue function in conjunction with low plasma concentrations of cortisol and thyroid hormones. The present study therefore aimed to determine whether maternal dexamethasone (a synthetic corticosteroid) administration could improve thermoregulation in premature lambs to the extent that they become similar to term lambs. Lambs were either delivered by caesarean section into a war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 23 publications
(26 reference statements)
1
29
0
4
Order By: Relevance
“…The effect of delivery temperature on leptin mRNA was not apparent in lambs born to ewes that had been administered with dexamethasone for 2 d before delivery. Dexamethasone promotes maturation of brown adipose tissue to the extent that lambs born 1 week prematurely are better able to effectively thermoregulate and have more UCP1 (14). Clinical studies have demonstrated plasma leptin to be increased 3-fold after maternal steroid treatment (13), although whether this was because of a change in leptin secretion by the placenta or fetal adipose tissue has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of delivery temperature on leptin mRNA was not apparent in lambs born to ewes that had been administered with dexamethasone for 2 d before delivery. Dexamethasone promotes maturation of brown adipose tissue to the extent that lambs born 1 week prematurely are better able to effectively thermoregulate and have more UCP1 (14). Clinical studies have demonstrated plasma leptin to be increased 3-fold after maternal steroid treatment (13), although whether this was because of a change in leptin secretion by the placenta or fetal adipose tissue has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a reduction in leptin mRNA in cool-delivered dexamethasone-treated lambs may be indicative of increased mRNA stability (24) and override any peripheral signals, such as increased catecholamines, which would normally inhibit leptin secretion (25). These temperature-related differences in leptin mRNA abundance could have contributed to the improved thermoregulation after cesarean section birth into a cool ambient temperature (14). To this extent, an acute increase in plasma leptin improves the ability of neonates to maintain colonic temperature (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations